Photoelectron angular distribution studies for two spin–orbit-split components of Xe 3d subshell: a critical comparison between theory and experiment. (18th May 2021) - Minemoto, S; Teramoto, T; Majima, T; Mizuno, T; Mun, J H; Park, S H; Kwon, S; Yagishita, A; Toffoli, D
Abstract: The photoelectron angular distribution asymmetry parameters β of the Xe 3d subshell were investigated using an x-ray free-electron laser (XFEL) at photon energies of 750 and 800 eV. Owing to the perfect polarization of the XFEL and two-dimensional momentum imaging capability of our velocity map imaging spectrometer, we determined the β values with high accuracy. The β values were also investigated based on relativistic time-dependent density functional theory calculations of up to 900 eV of photon energies. By comparing all the available experimental results including our data with the most reliable theories on the photon energy dependence of the β parameters, serious differences are noted between the experiments and theories. Further studies on resolving this difference will provide new insight into the photoionization processes of the deep inner shells.